TOWARD PEOPLES' SPIRITUALITY CHRISTIAN RESPONSE TO THE RISING FUNDAMENTALISM : . - Kalliath, Antony (Journal of Dharma, 2002)
Bharath, the land of Mahatma Gandhi and Buddha, well renowned for her non-violence (ahimsa) and tolerance world over, has become "Bloody India" in the eyes of the world community (Time March 11, 2002). The horrendous torching of the kar sevaks (Hindu activists) in the train at Godhra while returning from the holy site at Ayodhya (Feb 27, 20Q2), and the following frenzy of slaughter of innocent Muslims and the destruction of their properties show how religious fundamentalism can acquire diabolic proportions beyond wild imaginations possible. The people who perpetrated the Gujarath violence wounded the very pride and identity of the nation in its own eyes and those of the civilized nations.